Pembuatan Dry Yeast (Lab Scale) Bag.1 - Koentoro Soebijarso (Balai Besar Kimia dan Kemasan, 1977)
Yeast can be used for many purposes , in the fermentation industries, bakeries, alcoholic beverages , etc , Yenst can be also used for · Saccharification and fermentation in home industries, and also it can be used as cattle food. The protein conten is about 45-52 % dry matter (White)1-2,6 % fats and a good sources of Calsium, Iron, and Phosphor. Inthis experiment active dry yeast Temperature, pH, medium and exponentialfeeding and several, drying experiment was conducted within Lab-scaIe unit,in making mass production, drying was made by drum/spraydrying.